2007
DOI: 10.1021/jp072344i
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Vapor−Liquid Interfacial Tension of Nonassociating and Associating Fluids with the SAFT-VR Density Functional Theory

Abstract: The SAFT-VR DFT Helmholtz free energy density functional [Gloor, G. J.; Jackson, G.; Blas, F. J.; Martín del Río, E.; de Miguel, E. J. Chem. Phys. 2004, 121, 12740] is used to describe the vapor−liquid interface of nonassociating and associating molecules ranging in size from small molecules to long chains. The functional, which is based on the statistical associating fluid theory for attractive potentials of variable range (SAFT-VR) description of the homogeneous fluid [Gil-Villegas, A.; Galindo, A.; Whitehea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
107
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(113 citation statements)
references
References 64 publications
6
107
0
Order By: Relevance
“…Gloor et al, [40][41][42] however, proposed a prescription to consistently apply the DFT with these bulk-phase equations of state. It was shown that a DFT treatment of the dispersive attraction can be established based on perturbation theory, while any ͑small͒ difference between this dispersion term and the dispersion term of the engineering equation of state can with sufficient accuracy be described with a local density approximation ͑LDA͒.…”
Section: Introductionmentioning
confidence: 99%
“…Gloor et al, [40][41][42] however, proposed a prescription to consistently apply the DFT with these bulk-phase equations of state. It was shown that a DFT treatment of the dispersive attraction can be established based on perturbation theory, while any ͑small͒ difference between this dispersion term and the dispersion term of the engineering equation of state can with sufficient accuracy be described with a local density approximation ͑LDA͒.…”
Section: Introductionmentioning
confidence: 99%
“…For a recent overview of the numerous applications of DFT to pure fluids, the reader is referred to some of our previous publications [57][58][59][60] and to the recent work of Gross…”
mentioning
confidence: 99%
“…The attractive non-local term was calculated using a mean-field approximation. Moreover, they considered the capillary-wave "correction"by means of a mode-coupling theory for the mean-square roughness of the interface for the SAFT-VR approach which can be formulated as a DFT 59,60 ; the accuracy of this approximation has been confirm by comparison with the simulation data for vapour-liquid surface tension of square-well fluids of variable range 96 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22] Based on SAFT EoS, several groups have developed DFT models and further used them to describe the phase behaviors of mixture as well as interfacial tensions. Gloor et al [23][24][25] developed a DFT model on the basis of SAFT-VR with a local density approximation, and the model accurately predicts the interfacial tension. Based on perturbed-chain polar statistical associating fluid theory (PCP-SAFT), Gross 26 proposed a DFT reproducing the surface tension of non-polar and polar substances.…”
Section: Introductionmentioning
confidence: 99%